2015
DOI: 10.1007/s00277-015-2403-2
|View full text |Cite
|
Sign up to set email alerts
|

Programmed death-1 (PD-1), programmed death-ligand 1 (PD-L1), and EBV-encoded RNA (EBER) expression in Hodgkin lymphoma

Abstract: Programmed death-1 (PD-1) and programmed death-ligand 1 (PD-L1) are new targets in cancer immunotherapy. PD-1 protein is an immune checkpoint expressed in many tumors. Epstein-Barr virus (EBV) is present in malignant Hodgkin/Reed-Sternberg (HRS) cells in approximately 40-50 % of Hodgkin lymphoma (HL). The aim of this study is to evaluate the clinical and prognostic importance of PD-1 and/or PD-L1 in HL and also to determine the association between EBV-encoded RNA (EBER) and PD-1/PD-L1. Formalin-fixed, paraffin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
57
3
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 41 publications
7
57
3
5
Order By: Relevance
“…A more recent study reported PD-L1 positivity in only 20% of examined HL patients, with staining intensities and patterns not further specified. 68 In contrast with findings in DLBCL, PD-L1 expression is not increased in EBV + patients. 35,68,70 RS cells and variants appear to lack PD-1 expression, suggesting a potentially mutually exclusive expression pattern with PD-L1.…”
Section: Pd-l1/ Pd-1 Expression On Hl and Pmbcl Cellscontrasting
confidence: 43%
See 2 more Smart Citations
“…A more recent study reported PD-L1 positivity in only 20% of examined HL patients, with staining intensities and patterns not further specified. 68 In contrast with findings in DLBCL, PD-L1 expression is not increased in EBV + patients. 35,68,70 RS cells and variants appear to lack PD-1 expression, suggesting a potentially mutually exclusive expression pattern with PD-L1.…”
Section: Pd-l1/ Pd-1 Expression On Hl and Pmbcl Cellscontrasting
confidence: 43%
“…Another study found median OS and disease-free survival (DFS) to be shorter in patients with PD-1 compared to those without PD-1 expression, as well as in patients with PD-L1 expression compared to those without, but none of these differences were statistically significant. 68 Interestingly, co-expression of PD-1 and PD-L1 emerged as an independent risk factor for prognosis (OR 6.9, 95 % CI 1.9-24.3), and both OS and DFS were significantly reduced among patients with PD-1/PD-L1 coexpression compared to both PD-1 and PD-L1 negative patients. Koh et al reported that patients with tumor PD-L1 expression were more likely to have a low level of lactate dehydrogenase (P=0.024) than PD-L1-negative patients, but neither PD-L1 nor PD-L2 expression were significantly associated with OS (P=0.477 and P=0.676) 69 (Table 6).…”
Section: Pd-l1/ Pd-1 On Hl/pmbcl-associated Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Previous studies have indicated that high leukocyte PD-1 expression may be associated with inferior overall survival (OS). [11][12][13][14] However, in only 1 of these did PD-1 remain associated with poorer OS after adjustment for parameters included in the IPS. 11 In 1 study, high PD-L1 expression (on either HRS cells or leukocytes) was associated with inferior OS when coexpressed with high PD-1.…”
Section: Introductionmentioning
confidence: 99%
“…11 In 1 study, high PD-L1 expression (on either HRS cells or leukocytes) was associated with inferior OS when coexpressed with high PD-1. 13 9p24.1 gene amplifications and expression of PD-1 ligands on HRS cells were associated with inferior prognosis in 1 study. 8 In contrast, 2 other studies found PD-1 ligand expression on HRS cells to have no prognostic impact.…”
Section: Introductionmentioning
confidence: 99%